The Feasibility of a Patient-Centered Medical Home to Treat Pregnant Women With Opioid Use Disorder: A Pilot Study [19Q]. (May 2017) - Mokhtari, Neggin; Bobby, Stephanie; Chang, Judy C.; Gedekoh, Robert; England, Michael; Krans, Elizabeth E.
Abstract : INTRODUCTION: The patient-centered medical home (PCMH) is a healthcare model intended to improve healthcare quality while reducing costs. Pregnant women with opioid use disorder (OUD) require intensive healthcare resources. Therefore, a pilot study was conducted to establish the feasibility of a buprenorphine PCMH for pregnant women with OUD. METHODS: The Pregnancy Recovery Center (PRC) was created by five buprenorphine-licensed obstetricians and one addiction certified nurse in 2014. The PRC provides co-located buprenorphine, prenatal care, counseling, and social services support through a PCMH approach. Feasibility was measured by the ability to enroll, treat and retain patients. Successful completion (retention) was defined by negative drug screens, compliance with prenatal care, buprenorphine and counseling appointments. Additional outcomes were also compared between PRC vs non-PRC buprenorphine patients. RESULTS: Of 50 pregnant women enrolled from July 2014 to July 2015, 32 (64%) women successfully completed the program. The mean age was 28.1 years and 95.5% of women were white. Among 32 PRC and 78 non-PRC patients, buprenorphine dose at delivery was significantly higher for PRC vs non-PRC patients (18.4 vs 14.7 mg; P < .01), but neonatal abstinence syndrome (NAS) treatment rates were similar between the groups (46.2% vs 43.8%, P=.82). Fewer hospital charges for antepartum and delivery hospitalizations ($23, 554.00 vs $183, 703.00) were found for PRC vs non-PRC patients. CONCLUSION: A buprenorphine PCMH is feasible and may improve maternal and neonatal outcomes for pregnant women with OUD. Future large-scale clinical trials are needed to compare outcomes associated with alternative healthcare delivery models such as PCMHs for this population.